Teoria de L. S. Vigotski e o atendimento educacional aos transtornos globais do desenvolvimento : da identificação da conduta desviante à formação do homem cultural - Gatto, Dayene Patrícia (2010)
This research is the result of bibliographical study about Pervasive Developmental Disorders (PDD), which aims to investigate the assumptions about development and educational proposals which are presented in hegemonic terms and, in contrast, describe some of the assumptions of the School of Vygotsky to understanding issue based on other theoretical and methodological reference. This thesis is linked to the Research Project Historical-Cultural Psychology and Defectology: a study of the contributions / implications theoretical and methodological Soviet for the appropriation of verbal language for students with disabilities and the constitution of their subjectivities, coordinated by Prof. Dr. Sonia Mari Shima Barroco. The discussions here were woven guided by historical-dialectical materialism and systematized the vigotskian contributions to the education of people with different behavior due to organic peculiarities, for those arising from educational processes or the dynamics between them. This theory was taken in an attempt to consider the social totality to an appropriate understanding of human psyche also in deviant ways. First, we discuss some of the fundamental aspects and hegemonic assumptions addressed by the literature with respect to, among other factors, diagnosis and education processes directed to the PDD. We made some reflections on the social practice today, assuming that the intrapsychological content was, at first, extrapsycologically based, seeking to address issues of social and historical complexity and its dimensions for the proper understanding of the specific cases of human development. We returned our attention to some further methodological discussions in relations between the historical and dialectical materialism and historical-cultural theory, about the crisis of psychology and on the assumptions and propositions of Vygotsky and his collaborators for the common and special education. We also work with the hypothesis that the vigotskyan elaborations is fruitful for a better understanding of the constitution of the human in man, even when it presents itself, in its development, different from their peers. We turned our efforts, then, to understand some aspects of the methodology advocated by Vygotsky, interested in finding resources theorists who assert the possibility of a historicized understanding of the psyche also in the outliers, which will assist in an evaluation practice and forms of educational intervention. Finally, we explore the contributions of Vygotsky's school for the humanization of people with PDD, highlighting the important contributions of this theoretical school in relation to fund raising theoretical-methodological that signaled the possibility of a historicized understanding of the psyche in the case of PDD, and enriched educational interventions, assuming as north the humanization as much as possible, with views to what these students can become with the necessary support and education and what educators can not do without. We complemented our discussion the understanding that the Historic-Cultural Theory in general and with regard to Defectology, can support a theoretical-methodological aiming for a maximum possible development of the people under the condition of PDD.